1992
DOI: 10.1007/bf00124261
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex, t-complex, and leukemia

Abstract: In experimental models, leukemia was the first disease shown to have an association with the major histocompatibility complex (MHC) genes. In humans, several allelic human-leukocyte antigen (HLA) associations also have been recognized. In addition to allelic associations, atypical HLA segregation patterns have been observed in leukemic families. These include a higher frequency of HLA-identical unaffected siblings, increased HLA homozygosity and increased maternal HLA-DR identity. These observations suggest pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 80 publications
(10 reference statements)
0
9
0
2
Order By: Relevance
“…The t complex of genes, which confers cancer susceptibility, is transferred preferentially through fathers in a phenomenon called segregation distortion. 18 The t complex contains both TCP-1 and MnSOD, both of which were identified in this study. Figueroa et al 19 proposed that since Mn SOD is a mitochondrial enzyme, and mitochondria are important for sperm motility, MnSOD is in fact the gene within the t complex that is responsible for the observed segregation distortion.…”
Section: Figurementioning
confidence: 63%
See 1 more Smart Citation
“…The t complex of genes, which confers cancer susceptibility, is transferred preferentially through fathers in a phenomenon called segregation distortion. 18 The t complex contains both TCP-1 and MnSOD, both of which were identified in this study. Figueroa et al 19 proposed that since Mn SOD is a mitochondrial enzyme, and mitochondria are important for sperm motility, MnSOD is in fact the gene within the t complex that is responsible for the observed segregation distortion.…”
Section: Figurementioning
confidence: 63%
“…24 In this chromosomal region there are genes for two disorders, in addition to ALS, and two commonly elicited signs in sufferers, that co-segregate in some families with schizophrenia (Table 2). Therefore, heterogenous rearrangement of, deletions in, or abnormal regulation of genes within the chromosomal region [16][17][18][19] segregation distortion…”
Section: Figurementioning
confidence: 99%
“…It is surprising that this fact has been frequently overlooked in similar association studies of human leukaemia. In view of the findings in animal models, previous human studies in leukaemia, and the recessive nature of the putative leukaemia susceptibility gene(s) within the MHC (Dorak and Burnett, 1992), HLA association studies in human cancer should investigate the frequencies of genotypes including homozygous ones. If homozygosity had been examined, the previously observed significant but relatively weak DR53 association in CLL (Dyer et al, 1986) might have been stronger.…”
Section: Discussionmentioning
confidence: 99%
“…The first study on HLA in human leukemia demonstrated an increased frequency of HLA-A2 in ALL in 1967 .From that date many previous studies have demonstrated some significant differences in HLA allele frequencies in leukemic patients and normal subjects which had reported by Diase et al (2015) and others (14,15,16). In our study, significant positive association with the disease, in patients compared to controls, was found for two alleles: HLA-DRB1*013.Also there were moderate difference among DRB1*06 DRB1*14, and *15.…”
Section: Discussion:-mentioning
confidence: 87%
“…Diase et al (2015) had reported that HLA-DRB1*13, which showed a decrease in patients, should be protective against ALL (14). The findings that were demonstrated also by Dorak et al (2013),who reported that the frequency of the HLA-DRB1*13 allele was lower in male patients of leukemia (15).…”
Section: Discussion:-mentioning
confidence: 94%